Effectiveness of Drill Method in Madrasah Diniyyah Ketapangtelu Lamongan (New Normal Era) - Nur Iftitahul Husniyah; Purwanto Purwanto (EDUCATIO : Journal of Education, 2021)
: The Drill method is a learning method that emphasizes training activities that are carried out repeatedly to master certain abilities or skills. Skills that can be developed through drills include motor skills through Arabic writing. Through the repetition given, students will increasingly master the skills learned step by step until the skills can be mastered thoroughly. The drill method in Islam is a way of presenting Islamic Religious Education lesson materials by training students repeatedly and seriously in the form of oral, written, or physical activity so that students have high dexterity or skills in mastering the subject matter, strengthening a association or perfecting a skill to make it permanent. For almost a year, education around the world has been paralyzed due to the Covid-19 pandemic, the strengthening of Islamic education in the New Normal Era in Ketapangtelu Lamongan Village is re-applied into the religious-based learning process, namely by starting students re-entering Madrasah Diniyah in Ketapangtelu Lamongan Village. During the Covid pandemic, many subject matter was forgotten by students, especially lessons that were rote in nature such as Al-Qur'an hadith, Nahwu Shorof and so on, so the Drill Method was considered very appropriate to start again learning that had been suspended for a long time. In March 2021, Madrasah Diniyah Ketapangtelu officially reopened the learning process while still adhering to the health protocol.